2013
DOI: 10.1080/10584587.2013.852936
|View full text |Cite
|
Sign up to set email alerts
|

CaCu3Ti4O12 Ceramic Synthesized by Sonochemical-Assisted Process

Abstract: CaCu 3 Ti 4 O 12 powders were synthesized by sonochemical-assisted process via a precursor solution of calcium nitrate trihydrate, titanium isopropoxide and copper nitrate trihydrate. The reaction process was conducted with the assistance of intense sonication using Sonics Model VCX 750 until the completely precipitated product was reached, followed by calcinations process. The physical microstructures, morphologies of as-prepared samples were characterized by X-ray diffraction, scanning electron microscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Wongpisutpaisan et al [39] synthesized the giant dielectric-constant material CCTO by aonochemical-assisted process containing stoichiometric amounts of the metal nitrate, at a shorter reaction time than that of a conventional solid-state reaction. Synthesis from a solution affords intimate and homogeneous mixing of the metal ions at the atomic scale.…”
Section: Synthesis Methods Of Cctomentioning
confidence: 99%
See 1 more Smart Citation
“…Wongpisutpaisan et al [39] synthesized the giant dielectric-constant material CCTO by aonochemical-assisted process containing stoichiometric amounts of the metal nitrate, at a shorter reaction time than that of a conventional solid-state reaction. Synthesis from a solution affords intimate and homogeneous mixing of the metal ions at the atomic scale.…”
Section: Synthesis Methods Of Cctomentioning
confidence: 99%
“…The diameter of the multiphase CCTO powders was 500 nm as obtained by SEM, and the average crystalline size calculated using the Scherrer’s equation from the full-width-at-half-maximum (FWHM) of the strongest diffraction peak (220) was ∼75 nm. Wongpisutpaisan et al [39] observed that as the frequency increased over 1 kHz, the ɛ rapidly decreased. In addition, the higher ɛ values at lower frequency could be related to the possibility of the presence of interfacial polarization.…”
Section: Synthesis Methods Of Cctomentioning
confidence: 99%
“…The initial concentration of BPA c 0 was kept fixed. The apparent pseudo first-order rate constant k 1 …”
Section: Methodsmentioning
confidence: 99%
“…Also, their availability is easy with low cost. Therefore, doping of Cu ions was chosen for enhancement of photocatalytic activity 23 . Important points in the semiconductor photocatalyst materials are band gap energy between CB and VB and potential energy levels of CB and VB.…”
Section: ) Mechanism For Doped Metal In Tio2mentioning
confidence: 99%
“…It is found that the phytochemical present in fruit peels 20 are responsible for synthesis of Cu-doped nanoparticles that itself acts as stabilizers in synthesis 15 thus special capping agent/ stabilizer is not required. As plant extract is used instead of organic chemicals, this method omits the use of conventional chemicals like isopropyl alcohol 21 , ethanol 22 , polyvinyl alcohol 23 , etc. On the other hand, plant extract is prepared in water with waste peels.…”
Section: Introductionmentioning
confidence: 99%